Coping styles and hopelessness in mothers of children with autism in a group of institutions mothers of children with autism in a group of educational institutions for people with different abilities in Lima, 2014 - Chávez Urbina, Sandra Cecilia (2016)
The present investigation had as aim determine the relation between the styles of coping and hopelessness in mothers of children with autism of in a group of educational institutions of people with different skills in Lima. The study sample consisted of 103 mothers of four educational institutions in Lima. For this, Questionnaire of Coping Estimation (COPE) and the Beck´s Hopelessness Scale (BHS). The main results obtained, there is a significant and negative relation between hopelessness and the unfocused coping style on the problem, and there is a significant and positive relation between hopelessness and the coping style avoidant, it is demonstrated with the test Spearman (Rho = -0.305, 0.204; p-valor = 0.000 < 0.01).